2017
DOI: 10.1038/s41564-017-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

DISARM is a widespread bacterial defence system with broad anti-phage activities

Abstract: The evolutionary pressure imposed by phage predation on bacteria and archaea has resulted in the development of effective anti-phage defence mechanisms, including restriction-modification and CRISPR-Cas systems. Here we report on a new defence system, DISARM (Defence Island System Associated with Restriction-Modification), that is widespread in bacteria and archaea. DISARM is comprised of five genes, including a DNA methylase and four other genes annotated as a helicase domain, a phospholipase-D (PLD) domain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
229
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(244 citation statements)
references
References 42 publications
12
229
2
1
Order By: Relevance
“…A total of 3758 genes for the DISARM system were identified. These included the Class I marker gene drmD (449 counts, 11.9% of DISARM genes), which encodes the SNF2-like helicase (23), as well as the Class II marker gene drmA (1020, 17.1% of DISARM genes), which encodes a protein with a putative helicase domain (23). Similarly, a total of 4598 genes representing all BREX types were identified in the metagenome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3758 genes for the DISARM system were identified. These included the Class I marker gene drmD (449 counts, 11.9% of DISARM genes), which encodes the SNF2-like helicase (23), as well as the Class II marker gene drmA (1020, 17.1% of DISARM genes), which encodes a protein with a putative helicase domain (23). Similarly, a total of 4598 genes representing all BREX types were identified in the metagenome.…”
Section: Resultsmentioning
confidence: 99%
“…These include adaptive immunity elements, such as the CRISPR-Cas systems, and innate immunity mechanisms, such as restriction-modification (RM) and toxin-antitoxin abortive infection (Abi) systems (18). Recent pangenomics studies have also identified novel defense systems that are widely distributed across bacterial taxa and are thought to play a role in anti-phage resistance (2023). These include the bacteriophage exclusion (BREX) system, coded by a 4-8 gene cluster, that provides resistance to Siphoviridae and Myoviridae tailed phages by inhibition of phage DNA replication (21), and other less well characterized systems such as the Thoeris, Shedu and Gabija elements that increase bacterial host resistance to specific groups of phages (22).…”
Section: Introductionmentioning
confidence: 99%
“…These include the well-studied restriction-modification and CRISPR-Cas systems, but there are numerous examples of defense by abortive infection (abi) and a plethora of new defense systems have been identified (86, 87). Some mycobacterial strains – including M. tuberculosis – have CRISPR-Cas-like arrays, although their functionality in defense and spacer acquisition is unclear (88); mycobacterial restriction-modifications have also been described (8992).…”
Section: Drivers Of Mycobacterial and Mycobacteriophage Dynamicsmentioning
confidence: 99%
“…In the replication step, bacteria have some well characterised counter attack strategies. Many of these defence strategies utilise DNA cutting, which can target the phage genome. Interestingly, some of the systems have been applied as advance tools in molecular biology.…”
Section: Arms‐race Strategy In the Interaction Between Bacteria And Pmentioning
confidence: 99%